Effect of Polycystic Ovaries on the Morphology of Uterus and Ovaries - Ambreen Usmani; Rehana Rehman; Bushra Wasim (ziauddin University, 2024)
Background: The presence of around 12 or more follicles in one or both ovaries with diameter ranging from 2-9mm is known as polycystic ovaries (PCO). This condition is associated with hyperandrogenemia and is one of the most common causes of infertility. Due to increase in use of ultrasonography as a diagnostic tool, more cases of PCOs are being timely reported. This has also lead to diagnosis of PCO in younger age group. Objective: To measure the effect of age on ovarian and uterine morphology in infertile women with polycystic ovaries (PCO). Methods: The cross sectional study was conducted in Karsaz Hospital, Karachi from January 2010 to March 2011. One hundred infertile women with PCOs were subdivided into age groups (years) 20-30 (group I) and 31- 40 (group II). The ovarian volume (OV), follicles count (FC) and size (FS), uterine area (UA) and endometrial thickness (Endo) were determined by ultrasonography. Unpaired t-test was applied to analyze the result. Results: The ovarian morphology showed a significant decrease in group II; the OV transabdominally was 14.26± 2.42 vs 10.56±1.0 (0.00) and transvaginally 14.93±2.55 vs 11.75±1.06 (0.00). The FC was 14.00±1.60 vs 12.3±0.78 (0.023) and FS was 8.23±8.9vs 3.29±6.9 (0.00). The uterine morphology however showed a significant increase in group II. The UA was 87.79±5.83 vs 118.71±22.83 (0.00) and endo was 0.46±0.10 vs 0.57±0.12 (0.00). Conclusion: Ovarian morphology variables include OV, FC and FS decrease in the older infertile group of women with PCOs but the uterine morphology variables showed an increase in area with thickening of endometrium in the older group. The association of endometrium and PCOs has not been reported in this part of the world and the study is an attempt to fill this gap and prevent misdiagnosis of endometrial cancer. Key Words: Polycystic Ovaries, Infertile, Ovarian Volume, Follicle Count, Follicle Size, Uterine Area, Endometrial Thickness.